Differential Extraction and Preliminary Identification of Polyphenols from Ugni candollei (White Murta) Berries - Natalia Fuentes-Jorquera; Roberto I. Canales; José R. Pérez-Correa; Jara Pérez-Jiménez; María Salomé Mariotti-Celis (MDPI AG, 2024)
Ugni candollei, commonly known as white murta, is a native Chilean berry with a polyphenol composition that has been underexplored. This study aimed to establish a comprehensive profile of white murta polyphenols using ultra-performance liquid chromatography electrospray ionization Orbitrap mass spectrometry (UPLC-ESI-ORBITRAP MS). Additionally, it compared the efficacy of conventional extraction methods with emerging techniques such as deep eutectic solvent (DES) extraction and hot pressurized water extraction (HPWE). The analysis tentatively identified 107 phenolic compounds (84 of them reported for the first time for this cultivar), including 25 phenolic acids, 37 anthocyanins, and 45 flavonoids. Among the prominent and previously unreported polyphenols are ellagic acid acetyl-xyloside, 3-p-coumaroylquinic acid, cyanidin 3-O-(6'-caffeoyl-glucoside, and phloretin 2'-O-xylosyl-glucoside. The study found HPWE to be a promising alternative to traditional extraction of hydroxybenzoic acids, while DES extraction was less effective across all categories. The findings reveal that white murta possesses diverse phenolic compounds, potentially linked to various biological activities.